Analisis Respons Struktur Portal Baja Bertingkat Akibat Kandungan Frekuensi Gempa Yang Berbeda - Afisha, Elly; Suryanita, Reni; Yuniarto, Enno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Indonesia is one of the countries that located in the quake zone. But not all earthquakes that occur is a devastating earthquake. Some earthquake parameters that affect the level of damage from a building structure are the peak ground acceleration, response spectrum value, earthquake duration, and earthquake frequency content. The earthquake frequency content parameters were considered the most influential on structural damage. The objective of this research is to get the response from the structure of multilevel steel portals such as displacement, inter-story drift, velocity, acceleration, and to analyze the displacement limit based on SNI 1729-2012. The reviewed structure is an open frame steel building model that is into 5 levels, 10 levels, and 15 levels. This study use time history analyses with 9 earthquake recordings of the Kobe earthquake, Mexico earthquake, Nepal earthquake, Chile earthquake, New Zealand earthquake, Sumatera earthquake, Fredericksburg earthquake, Mentawai earthquake, and Northridge earthquake that has been grouped into low-frequency content, medium frequency content, and high-frequency content. The results showed that the structure responses such as displacement, velocity, and acceleration will increase with the increasing number of levels of the building structure. The inter-story drift the allowed level of the structure still qualified based on SN 1729-2012 where the allowed drift in 7 cm and the inter-story drift produced by the structure is still less than 7 cm. An earthquake with low-frequency content has an enormous influence on the structure response in all the level structure.Keywords: response structure, time history, frequency content